The development of a national approach to monitoring estuarine health based on multivariate analysis. (January 2020) - Clark, D.E.; Hewitt, J.E.; Pilditch, C.A.; Ellis, J.I.
Abstract: New Zealand has a complex coastal environment spanning a large latitudinal gradient and three water masses. Here we assess whether multivariate analyses of benthic macrofaunal community composition can be a sensitive approach to assessing relative estuarine health across the country, negating the need for regional indices and reducing reliance on reference sites. Community data were used in separate canonical analyses of principal coordinates to create multivariate models of community responses to gradients in mud content and heavy metal contamination. Both models performed well (R 2  = 0.81, 0.71), and were unaffected by regional and estuarine typology differences. The models demonstrate a sensitive and standardized approach to assessing estuarine health that allowed separation of the two stressors. This approach could be applied to other stressors, countries or regions. Highlights: A standardised and sensitive approach to assessing estuarine health is demonstrated. Sedimentation and metal contamination were the stressors of interest. The models can be applied across a range of estuary types and regions. The single-stressor approach allows the causes of degradation to be diagnosed. This approach could be applied to other stressors, countries or regions.